2021
DOI: 10.3390/molecules26206124
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phenylpyrrolidine Derivative: Synthesis and Effect on Cognitive Functions in Rats with Experimental Ishemic Stroke

Abstract: We performed an in silico, in vitro, and in vivo assessment of a potassium 2-[2-(2-oxo-4-phenylpyrrolidin-1-yl) acetamido]ethanesulfonate (compound 1) as a potential prodrug for cognitive function improvement in ischemic brain injury. Using in silico methods, we predicted the pharmacological efficacy and possible safety in rat models. In addition, in silico data showed neuroprotective features of compound 1, which were further supported by in vitro experiments in a glutamate excitotoxicity-induced model in new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Transient Middle Cerebral Artery Occlusion was conducted as previously described [ 17 ]. The rats were anesthetized initially using 3% isoflurane and maintained with a mixture of 2–2.5% isoflurane and 97.5–98% atmospheric air (EZ-7000 Classic System, E-Z Anesthesia ® Systems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient Middle Cerebral Artery Occlusion was conducted as previously described [ 17 ]. The rats were anesthetized initially using 3% isoflurane and maintained with a mixture of 2–2.5% isoflurane and 97.5–98% atmospheric air (EZ-7000 Classic System, E-Z Anesthesia ® Systems).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally these drugs affect memory processes. Previously, we carried out a chemical modification of Compound 2 by introducing a fragment of the potassium salt of taurine into its composition ( Scheme 1 , Compound 3 ) in order to increase the pharmacological efficacy in the treatment of post-stroke state in rats, as well as to obtain its water-soluble form suitable for the injection route of administration [ 17 ]. We have shown that Compound 3 better restores motor function and improves the cognitive abilities of animals in the post-stroke period, compared with the well-known water-soluble nootropic of the same class—piracetam (Compound 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…D-glutamate-treated CGNs and cortical neuron (CN) death are also considered classical neuronal excitotoxicity models. 9 Finally, middle cerebral artery occlusion (MCAO) is the most widely used cerebral ischemia model at present. Its pathogenesis is similar to that of human ischemic stroke, which gives it great importance in simulating cerebral ischemia and drug screening.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, our group has focused on discovering and developing new heterocyclic compounds that have nootropic, anti-inflammatory, and antidepressant activities. Our main goal is to develop effective medications for treating cognitive impairments, including ischemic stroke and its complications [ 1 , 2 , 3 , 4 ]. The recent COVID-19 pandemic highlighted the emerging need for these kinds of therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons is insufficient bioavailability and multiple side effects. Previously, we managed to increase the bioavailability of Phenotropil by introducing chemical modification, which led to the production of a water-soluble form based on taurine [ 1 ]. The same approach was shown for homotaurine [ 3 ].…”
Section: Introductionmentioning
confidence: 99%